Association of hepatitis viruses with hepatocellular carcinoma in Thailand - Tangkijvanich, Pisit; Hirsch, Petra; Theamboonlers, Apiradee; Nuchprayoon, Issarang; Poovorawan, Yong (Journal of gastroenterology, 1999)
Hepatocellular carcinoma (HCC) represents the most common form of malignant tumor among males in Thailand, an area endemic for hepatitis B virus (HBV) infection. Various risk factors have been associated with the development of HCC, among them exposure to certain toxins, and infection with hepatitis viruses, in particular HBV, as well as HCV in areas non-endemic for HBV infection. To examine the association of hepatitis viruses with HCC, our group investigated 101 patients who had been clinically, mainly via alpha fetoprotein level, and/or histologically diagnosed with hepatocellular carcinoma. We also examined 200 voluntary blood donors as controls. All subjects underwent serological tests for the presence of hepatitis B surface antigen (HBsAg) and anti-HCV with polymerase chain reaction (PCR) used for the detection of HBV and TT virus (TTV) DNA, and reverse transcription (RT)-PCR for the detection of HCV RNA and HGV RNA. Besides showing a clear preponderance of HCC among males, with a peak incidence the age group 51-70 years, the results obtained in the HCC patients demonstrated that the prevalence of HBV was 65%, four times that of HCV (17%), ten times that of HGV (6%), and seven times that of TTV (9%). In the controls, the prevalence of HBV was 0.5%; that of HCV, 0.5%: that of HGV, 5%; and that of TTV, 7%. These findings confirmed that hepatitis B virus was associated with the development of hepatocellular carcinoma among the Thai population, among whom case histories of chronic hepatitis and cirrhosis have also been encountered quite frequently.